Decolonizing the law curricula at Universities of Technology: The student’s perspective on content - Anwana, E. O. (South African Journal of Higher Education, 2022)
Universities of technologies (UoT’s) unlike most traditional universities in South Africa do not have law faculties and therefore only certain law modules such as commercial law, corporate law and other business law courses are offered to students. This article seeks to examine the extent to which Africanist epistemologies and perspectives should be included in the content of the business law curricula in UoT’s. The article applies the mixed methods research approach. Questionnaires with both closed and open-ended questions are administered to second year business law students of the Durban University of Technology (DUT). A semi-structured interview is conducted with third year business law students to ascertain their perceptions of the first year business law curricula and the content they would like to see included in the curricula. The results indicates that African students desire the inclusion of their lived experiences and epistemologies in the business law curricula. Students desire the inclusion of the indigenous jurisprudence of Ubuntu, traditional dispute settlement mechanisms, and other indigenous traditional contractual practices in the business law curricula. The findings will assist higher education managers and university curricula developers in developing an inclusive curricula that will meet the demands of African students.